Holly polyphenols attenuate liver injury, suppression inflammation and oxidative stress in lipopolysaccharide-challenged weaned pigs. Issue 1 (31st December 2022) - Huang, F. F.; Yang, Y.; Wang, L. M.; Wang, H.; Li, P.; Xiao, K.; Xu, X.; Liu, J. S.; Liu, Y. L.; Zhu, H. L.
ABSTRACT : It has been proved that polyphenols have positive effects against inflammatory response and oxidative stress. We investigated whether dietary supplementation of the holly polyphenols (HP) might relieve a liver injury induced by lipopolysaccharide (LPS) in weaned pigs. Twenty-four weaned pigs were fed diets containing 0 or HP and saline or LPS challenge in 2×2 factorial arrangement of treatments. On d 17, pigs were intraperitoneally injected with an LPS or saline. Dietary HP supplementation reduced plasma AST and GGT activities and liver MDA levels, increased plasma ALB and TP and liver GSH concentrations, and ameliorated LPS-induced liver histopathological damage. HP supplementation reduced plasma and /or liver TNF-α, IL-6 and IL-1β levels, and liver mRNA expression of IL-6, TNF-α and COX2 . Moreover, HP decreased the mRNA abundance of liver MyD88, TRAF6 and NOD1. These results suggest that HP supplementation attenuates liver injury induced by LPS in weaned pigs, and inhibits inflammatory response and oxidative stress.